2003
DOI: 10.1021/ar0200394
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Cyclopentannelation of Allene Ethers

Abstract: The variant of the Nazarov cyclization that makes use of allenyl ethers is suitable for the preparation of diverse, highly functionalized cyclopentenones. Three variants of the basic reaction, differing in the nature of the electrophile that is combined with the allene to prepare the precursor for the pentadienyl cation, are described. One variant, which utilizes an alpha,beta-unsaturated morpholino amide, has been successfully employed in an enantioselective version of the cyclopentannelation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
148
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(150 citation statements)
references
References 25 publications
0
148
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The Nazarov reaction is often catalyzed by a Brønsted-or Lewis acid; coordination of which generates the requisite oxyallyl cation 2, which undergoes a stereospecific 4π-electron-5-atom electrocyclization to generate the C-C bond. Electrocyclization reactions are powerful transformations in organic synthesis that have been exploited to construct new C-C and new C-N bonds in a stereospecific manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] The Nazarov reaction is often catalyzed by a Brønsted-or Lewis acid; coordination of which generates the requisite oxyallyl cation 2, which undergoes a stereospecific 4π-electron-5-atom electrocyclization to generate the C-C bond. Electrocyclization reactions are powerful transformations in organic synthesis that have been exploited to construct new C-C and new C-N bonds in a stereospecific manner.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] The most common approach is to intercept this intermediate with a nucleophile before deprotonation or elimination occurs. The resulting oxyallyl cation 25 triggers a [1,2] methyl shift to produce the more stable allylic cation 26. 35 They reported that exposure of divinyl ketone 9 to TiCl 4 produced 11 through the cationic olefin polycyclization of oxyallyl produces pentadienyl cation 24, which undergoes a 4π-electron-5-atom-electrocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the search for additional approaches toward rapid access to functionalized allenes for the intended [3+2] cycloaddition, we found that allenyl MOM ether, upon R deprotonation, has been used to prepare electron-rich allene derivatives en route to functional structures. 7 To our surprise, no study of these readily available, functionalized allenes in the presence of Au catalyst has been reported.…”
mentioning
confidence: 99%
“…In general, AcOH was the preferred proton source, and the reactions proceeded well at 0°C. For example, without purification of intermediate TMS ethers, 1-acetylcycloalkenes of different ring sizes underwent smooth reactions, and the cis-fused bicyclic ketones were formed in excellent yields (entries [6][7][8]. Notably, phenyl enone 5i participated in this two-step reaction as well, albeit in a low yield (entry 9).…”
mentioning
confidence: 99%
“…Allenes are versatile and valuable substructures in synthetic organic chemistry due to their characteristic structure and reactivity originated from the contiguous C¼C double bonds [25,26]. In particular, the axial chirality of allene derivatives has attracted much attention from organic chemists from the viewpoint of synthetic utility as chiral synthons.…”
Section: Isomerization Of Alkynoates To Allenoatesmentioning
confidence: 99%